2011
DOI: 10.1042/bj20101442
|View full text |Cite
|
Sign up to set email alerts
|

Structure and kinetic characterization of human sperm-specific glyceraldehyde-3-phosphate dehydrogenase, GAPDS

Abstract: hGAPDS (human sperm-specific glyceraldehyde-3-phosphate dehydrogenase) is a glycolytic enzyme essential for the survival of spermatozoa, and constitutes a potential target for non-hormonal contraception. However, enzyme characterization of GAPDS has been hampered by the difficulty in producing soluble recombinant protein. In the present study, we have overexpressed in Escherichia coli a highly soluble form of hGAPDS truncated at the N-terminus (hGAPDSΔN), and crystallized the homotetrameric enzyme in two ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…GAPDH structures (Mukherjee et al, 2010;Cook et al, 2009;Robien et al, 2006;Chaikuad et al, 2011;Querol-García et al, 2017;Moreau et al, 2017). Only the GAPDH structure with trehalose was significantly different from published structures.…”
Section: Figurementioning
confidence: 95%
“…GAPDH structures (Mukherjee et al, 2010;Cook et al, 2009;Robien et al, 2006;Chaikuad et al, 2011;Querol-García et al, 2017;Moreau et al, 2017). Only the GAPDH structure with trehalose was significantly different from published structures.…”
Section: Figurementioning
confidence: 95%
“…The structures of GAPDH from archaea, bacteria, and eukaryotes have been determined by x‐ray crystallography, and show that the NAD + cofactor is bound, despite not being added during protein purification. In mammalian GAPDH structures, two, three, or even four NAD + molecules have been observed per homotetramer. In addition, we recently showed that GAPDH was present as a mixture of NAD + ‐bound and NAD + ‐free species in solution by nano‐ESI/MS/MS studies .…”
Section: Structural Determinants Of Gapdhmentioning
confidence: 99%
“…Many structures of GAPDH from eukaryotes [ 5 , 6 , 7 ], bacteria [ 8 , 9 ], and archaea [ 10 , 11 ] have been reported. Eukaryotic and bacterial structures may have the same catalytic process, which is different from that of archaea.…”
Section: Introductionmentioning
confidence: 99%